Metagenome of Gut Microbiota of Children With Nonalcoholic Fatty Liver Disease - Zhao, Yuzhen; Zhou, Jianli; Liu, Jiaqi; Wang, Zhaoxia; Chen, Moxian; Zhou, Shaoming (Frontiers in Pediatrics, 2019)
Aim To investigate the intestinal flora of nonalcoholic fatty liver disease (NAFLD) in Chinese children and adolescents using metagenomic approach. Methods All participants underwent magnetic resonance spectroscopy (MRS) to quantify liver fat content. Hepatic steatosis was defined as MRS proton density fat fraction (MRS-PDFF) > 5%. A total of 58 children and adolescents were enrolled in this study, including 25 obese NAFLD patients, 18 obese non-NAFLD children and 15 healthy children. Stool samples were collected and analyzed with metagenomics. We used Shannon index to reflect the alpha diversities of gut microbiota. Wilcoxon rank sum test and Kruskal-Wallis test were performed to evaluate alpha diversities between groups. At last, the differences of gut microbiota composition and functional annotations between obese with and without NAFLD and healthy children were assessed by Kruskal-Wallis test. Results Significant differences in gut microbiota composition and functional annotations among three groups of children and adolescents have been observed. Deep sequencing of gut microbiota revealed high abundance of phylum Proteobacteria (Gammaproteobacteria) in obese NAFLD patients, comparing with the control group. Overall, obese children without NAFLD had less abundant Helicobacter and Helicobacter pylori. Compared to the control group, in obese children with NAFLD, the abundance of Bacteroidetes (Alistipes) were significantly reduced. Faecalibacterium prausnitzii was the only species representing difference between obese children with and without NAFLD. There were not significant differences in terms of alpha diversity among three groups. Functional annotations demonstrated that several pathways were differentially enriched between groups, including metabolism of other amino acids, replication and repair, folding sorting and degradation and glycan biosynthesis and metabolism. Conclusion Significantly differences are observed in gut microbiota composition and functional annotations between obese children with and without NAFLD in comparison to the healthy children group. The characteristic of gut microbiota in this study may contribute to a further understanding the gut-liver axis of pediatric NAFLD in China.